Grain consumption and risk of gastric cancer: a meta-analysis. (17th February 2020) - Wang, Tonghua; Zhan, Rui; Lu, Jiao; Zhong, Lu; Peng, XiaoJuan; Wang, Min; Tang, Shaohui
Abstract: This study evaluated the relationship between grain consumption and the risk of gastric cancer. A total of 19 studies met the inclusion criteria. For whole grain consumption, there was a 13% reduction in the risk of gastric cancer ( p  = .003), and a subgroup analysis showed that a large amount of whole grain consumption reduced the risk of gastric cancer by 44% ( p  < .001). For refined grain consumption, there was a 36% increase in the risk of gastric cancer ( p  < .001); a subgroup analysis showed that a large and a moderate amount of refined grain consumption increased the risk of gastric cancer by 63% ( p  < .001) and 28% ( p  < .001), respectively. A large intake of whole grains might be protective against gastric cancer, whereas the ingestion of refined cereals may be a risk factor for gastric cancer. Moreover, the risk of cancer increases with the increase of refined grain intake.